ChemInform Abstract: Convenient Approach to ω‐Aminoalkylthiophenes. Issue 33 (July 2016) - Shvydenko, Tetiana; Nazarenko, Kostiantyn; Shvydenko, Kostiantyn; Filimonchuk, Serhii; Vlasenko, Yurii; Tolmachev, Andrei; Kostyuk, Aleksandr
Abstract: The title thiophenes are prepared in three steps via synthesis of ω‐aminoalkylthiophene hydrobromides (V) from cyclic enaminoester, isothiocyanates, and haloketones.